Synthesis and characterization of green urethane non-isocyanate from oleic acid for wood composite application - Ghozali, Muhammad; Bakhri, Samsul; Triwulandari, Evi; Restu, Witta Kartika; Meliana, Yenny; Haryono, Agus; Septiyanti, Melati; Solihat, Nissa Nurfajrin; Lee, Seng Hua; Fatriasari, Widya; Antov, Petar (John Wiley and Sons, 2024)
Conventional polyurethane (PU) is usually synthesized by a reaction between isocyanate and polyol. The use of isocyanate compounds is associated with significant health and environmental problems. Therefore, it is necessary to develop an environmentally friendly alternative method for manufacturing PUs without isocyanate routes. The aim of this research work was to synthesize green urethane from oleic acid, which included the following three stages: the synthesis of epoxidized oleic acid (EOA), the synthesis of carbonated oleic acid (COA), and the synthesis of green urethane from oleic acid (UOA). The resulting product was characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR) analyses, and by determining the iodine number, oxirane number, and hydroxyl value. The results of FTIR and NMR showed that EOA was successfully synthesized. The optimum COA synthesis process was obtained on TBAB catalyst usage of 1 (wt/wt) at 140°C for 48 h with a 500-rpm stirring rate and CO2 gas flow rate of 0.2 mL/min with the resulting COA oxirane value of 0.00. The optimum condition of UOA synthesis through the aminolysis process resulted in the use of LiCl of 19.8 (wt/wt) at 70°C for 3 h with a stirring speed of 1200 rpm with a UOA hydroxyl number generated of 237.93 mg/mL.